Les études de genre dans le domaine de l’Antiquité. Les archives de la Bryn Mawr Classical Review (2000-2020) - Violaine Sébillotte Cuchet; Camille Noûs (Genre & Histoire)
The Bryn Mawr Classical Review, which has been operating with remarkable stability since its founding in 1990, is a valuable tool for reviewing studies in the history of women, gender, and sexuality in Antiquity. This article analyses the 377 reviews of publications identified as being in the field of gender and sexuality for the years 2000-2020, i.e. about 3% of the 11,354 reviews posted online. It analyses the evolutions over the period, the languages of scientific production on gender, the dominant themes and, critically, questions the disciplinary field that (mainly European and North American) scientists build, via this extremely well-distributed digital bibliographical tool. By adding important works that are absent from the Bryn Mawr Classical Review website, this article provides a valuable bibliographical tool for students as well as specialists